Sustainability in Energy and Buildings Proceedings of the 4th International Conference in Sustainability in Energy and Buildings (SEB´12) - Hakansson, Anne; Höjer, Mattias; Howlett, Robert J.; Jain, Lakhmi C. (Smart Innovation, Systems and Technologies, 2013)
This volume contains the proceedings of the Fourth International Conference on Sustainability in Energy and Buildings, SEB12, held in Stockholm, Sweden, and is organised by KTH Royal Institute of Technology, Stockholm, Sweden in partnership with KES International. The International Conference on Sustainability in Energy and Buildings focuses on a broad range of topics relating to sustainability in buildings but also encompassing energy sustainability more widely. Following the success of earlier events in the series, the 2012 conference includes the themes Sustainability, Energy, and Buildings and Information and Communication Technology, ICT. The SEB'12 proceedings includes invited participation and paper submissions across a broad range of renewable energy and sustainability-related topics relevant to the main theme of Sustainability in Energy and Buildings. Applicable areas include technology for renewable energy and sustainability in the built environment, optimisation and modeling techniques, information and communication technology usage, behaviour and practice, including applications.    .